2020
DOI: 10.1111/nmo.13964
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of putative interneurons in the myenteric plexus of human colon

Abstract: Background: The enteric nervous system contains multiple classes of neurons, distinguishable by morphology, immunohistochemical markers, and projections; however, specific combinations differ between species. Here, types of enteric neurons in human colon were characterized immunohistochemically, using retrograde tracing combined with multiple labeling immunohistochemistry, focussing on non-motor neurons. Methods: The fluorescent carbocyanine tracer, DiI, was applied to the myenteric plexus in ex vivo preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Immunohistochemically, they contain choline acetyltransferase (ChAT), leu-enkephalin (ENK) and, partly, SP (Brehmer et al 2005 ; Beck et al 2009 ). These chemical characteristics correspond to ascending motor and interneurons identified by Porter et al ( 1997 ) and Humenick et al ( 2021 ).
Fig.
…”
Section: Structure Of Human Myenteric Neuronssupporting
confidence: 78%
See 3 more Smart Citations
“…Immunohistochemically, they contain choline acetyltransferase (ChAT), leu-enkephalin (ENK) and, partly, SP (Brehmer et al 2005 ; Beck et al 2009 ). These chemical characteristics correspond to ascending motor and interneurons identified by Porter et al ( 1997 ) and Humenick et al ( 2021 ).
Fig.
…”
Section: Structure Of Human Myenteric Neuronssupporting
confidence: 78%
“…The other method deciphered target tissues of axonal projections by tracing techniques (most successful with the carbocyanine tracer DiI; Wattchow et al 1995 , 1997 ; Porter et al 1997 , 2002 ; Humenick et al 2019 , 2021 ). These studies demonstrated projection distances for motoneurons of about 1 to 2 cm (for ascending and descending pathways to circular and longitudinal muscle, respectively) as well as for interneurons of about 4 to 7 cm (for ascending and descending interneurons, respectively).…”
Section: Structure Of Human Myenteric Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…Long descending projections run for up to 70 mm down the colon, whereas long ascending neurons project for up to 43 mm. These long descending and ascending myenteric neurons would act as putative interneurons in polysynaptic polarized reflex pathways involved in propulsion and other possible intestinal functions [ 48 ].…”
Section: Organization Of the Ensmentioning
confidence: 99%